Protection of Rubber Plantation Managers Perspektif Mui Fatwa No.85 Dsn-Mui/Xii/2012 (Case Study of Gotting Julu Village, Huristak District, Padang Lawas Regency) - Fauzan Azhari Hasibuan; Rahmad Efendi (Warmadewa Press, 2024)
The purpose of this research was to find out how to protect rubber plantation managers in Gotting Julu village, Huristak District, North Padang Lawas Regency. This research is carried out using a type of field research, which is direct research and interaction with the research object. In analyzing the researches uses qualitative descriptive, namely a research procedure that explains the reality obtained from the field. Data collection was carried out by interview and observation methods to meet the results of this study. The results of this study found. 1) the land owner violates the agreement that has been mutually agreed upon and does not provide equipment at all to cultivate 2) the land owner cuts the percentage that is determined for the rubber plantation manager 3) the contract carried out between the owner and the rubber plantation cultivator in Gotting Julu village is only carried out verbally with the principle of kinship, the reason for the rubber plantation land owner in carrying out this cooperation is because of the manpower that is no longer able to process, the time is not there, and to help help Meanwhile, the reason for farmers is because they do not have land, lack of economy. The application of rubber farmer profit sharing that occurred in Gotting Julu Village, Huristak District, Padang Lawas Regency was reviewed from several aspects such as the method of agreement or contract was only carried out orally and was not attended by witnesses, the land owner did not provide tools for the manager.